Effect of Triangle Fin Inclination Angle and Aluminum Metal Foam on Melting Process in A Vertical Latent Heat Energy Storage System - Gürsoy, Emrehan; Gürdal, Mehmet; Gedik, Engin (Journal of Scientific, Technology and Engineering Research, 2025)
The main objective of this numerical study is to investigate the effect of triangle fin inclination angles (IAs) on the melting process in a Latent Heat Thermal Energy Storage (LHTES) system designed as a vertical rectangular cavity with and without metal foam (MF). In the cases, paraffin wax phase change material (PCM) filled the entire domain, and the Brinkman-Darcy-Forchheimer model, assuming local thermal equilibrium (LTE), and the enthalpy-porosity method were employed to simulate the melting process. In total, 14 different cases were analyzed and the results were validated with literature at high accuracy. Melting time, stored energy, temperature variation, and hydrodynamical behavior of the melting derived from numerical simulations are provided. The findings highlight that utilizing MF has reduced the melting time by 87.5 times and it provided a uniform melting due to enhancing the thermal conductivity of the domains. Also, MF has varied melting behavior and the shortest melting time was realized at 120° without MF, while cases with MF experienced the earliest melting at R-60°. However, using MF decreased the stored energy amount at the rate of 5.69% while the highest energy storage was realized without MF of R-60° as 54.83 kJ.m-1.
Keywords: Energy; Gizli ısı termal enerji depolama; Erime; Gözenekli yapı; Faz değiştiren madde; Üçgen kanatçık; Latent heat thermal energy storage; Melting; Metal foam; Phase change material; Triangle fin; Enerji Üretimi, Dönüşüm ve Depolama (Kimyasal ve Elektiksel hariç); Energy Generation, Conversion and Storage (Excl. Chemical and Electrical); Enerji